Answer:
D
Step-by-step explanation:
2(3x + 5) =
2 x 3x + 2 x 5 =
6x + 10
<em>Hope that helps! :)</em>
<em></em>
<em>-Aphrodite</em>
Answer:
Answer: Third option is the right answer.
Step-by-step explanation:
First we the write the expression
![(a+b)(a^{2}+b^{2}-ab)](https://tex.z-dn.net/?f=%28a%2Bb%29%28a%5E%7B2%7D%2Bb%5E%7B2%7D-ab%29)
Now teacher says that the product of these polynomials will result in the sum of ![a^{3}+b^{3}](https://tex.z-dn.net/?f=a%5E%7B3%7D%2Bb%5E%7B3%7D)
Now the teacher ask if we put the value of a = 2x and b = 1 then what will be the expression look like.
![(2x+1)\left [ (2x)^{2}+(1^{2})-(2x)(1)\right ]](https://tex.z-dn.net/?f=%282x%2B1%29%5Cleft%20%5B%20%282x%29%5E%7B2%7D%2B%281%5E%7B2%7D%29-%282x%29%281%29%5Cright%20%5D)
=![(2x+1)(4x^{2}+1-2x)](https://tex.z-dn.net/?f=%282x%2B1%29%284x%5E%7B2%7D%2B1-2x%29)
So third option is looking like our expression.
Answer:
5,022 Students
Step-by-step explanation:
All you have to do it multiply!
Like so:
81*62= 5,022
It reachs 5800 population in 1960 if i am not wrong. i'll check this out tomorrow right now i do not have enough time for it.
(1/3)x=3+(1/4)x
is the same as
(4/12)x=(36/12)+(3/12)x
subtract the 3/12x from each side
(1/12)x=36/12
multiply by 12 on each side
x=36